Ab initio Study of Structure, Electronic and Magnetic Properties of Graphene-M (M=Cr, Mn, Fe, Cu, Zn) using Density Functional Theory - Sukma Hutama, Aulia
Graphene is one of several carbon allotropes beside diamond and graphite. Material based on graphene have potential uses for various application. Since its discovery, it has been studied and understood as a candidate for replacing conventional materials such as silicon based materials as used in semiconductor technology. The interesting point is that graphene's properties can be altered with the addition of several adsorbent atom (adatom). A class of metal that can be used for altering graphene's properties are transition metal. In this research, the series of calculation of system involving graphene and transition metals have been done. The calculation includes determining the most stable structure energetically, calculating their electronic properties such as band structure and density of states and determining their magnetic properties from graphene-metal and pure graphene as comparison. The transition metals that have been successfully calculated are Mn, Fe, Cu and Zn. Softwares that are used is SIESTA for calculation and XCrysDen for visualization. The result shows that each transition metal atom gives different influence on graphene's properties. The result of bond energy shows that bond between graphene and metal atom is covalent bond. Addition of Fe, Mn and Cu alter graphene from semimetal into metal. Addition of Zn alters graphene into semiconductor, conductor and semimetal depends on concentration of Zn on graphene' surface. The transition metal addition on graphene also alters the magnetic properties, from diamagnetic into paramagnetic for Fe and Mn while Cu and Zn retain its diamagnetism. From these result, it was concluded that these systems have potential application for magnetic or electronic device.